Adjuvant radiotherapy treatment of chordoid glioma: a case report with a literature review - Cuccia, Francesco; D’Alessandro, Salvatore; Messina, Marco; Tringali, Giovanni; Craparo, Giuseppe; Blasi, Livio; Azzarello, Francesco; Carruba, Giuseppe; Ferrera, Giuseppe (Frontiers in Oncology, 2025)
BackgroundChordoid glioma is a rare World Health Organization (WHO) Grade II brain tumor located near the third ventricle. Fewer than 100 cases have been reported in the literature, and surgery represents the main treatment option. Due to its typical location, complete surgical resection is uncommon, and the role of adjuvant radiotherapy remains controversial.MethodsBased on a case report, we performed a literature review focused on the potential role of adjuvant radiotherapy for chordoid glioma. We summarized data on patient characteristics, surgical approach and extent of resection, radiotherapy technique and dose, and clinical outcomes.ResultsA total of 18 patients from 14 studies were identified. Stereotactic treatments were used more frequently than conventional external beam radiotherapy, with doses ranging from 11.5–18 Gy and 45–59.4 Gy, respectively, and a median local control time of 26 months. Five patients developed disease recurrence after a median of 22.4 months. In the present case, the patient received adjuvant conventional radiotherapy (59.4 Gy/33 fractions) and remains alive after 12 months of follow-up with no major side effects.ConclusionsFrom the available evidence, modern radiotherapy may be considered a therapeutic tool that combines less invasive surgical procedures with improved local control, potentially reducing the risk of severe postoperative complications. Larger studies with longer follow-up periods are needed.